A Qualitative Study of Acculturation and Diabetes Risk Among Urban Immigrant Latinas: Implications for Diabetes Prevention Efforts. (September 2014) - O'Brien, Matthew J.; Shuman, Sara J.; Barrios, Dulce M.; Alos, Victor A.; Whitaker, Robert C.
Purpose: The purpose of this qualitative study was to understand how acculturation influences diabetes risk among urban immigrant Latinas (Hispanic women). Methods: Five focus groups were conducted with 26 urban immigrant Latinas who were at high clinical risk for developing diabetes. The focus group sessions were audiotaped and transcribed verbatim. The authors independently analyzed transcripts using an inductive method of open coding and established themes by consensus. Results: All participants were foreign born and had low levels of acculturation. During the acculturation process, they noted changes in their lifestyle behaviors and the family context in which those behaviors are shaped. They reported that since living in the United States, their improved economic circumstances led to increased consumption of less healthy foods and beverages and a more sedentary lifestyle. They also described changing family roles and responsibilities, including working outside the home, which constrained healthy food choices. However, they perceived that their position of influence within the family offered opportunities to help family members prevent diabetes. Conclusions: Lifestyle interventions to prevent diabetes in Latinas should address their acculturation experiences, which affect family functioning and health behaviors related to diabetes risk. For example, given the perceived link between Latinas' improved economic circumstances and their diabetes risk, prevention programs should incorporate strategies to help Latinas avoid adopting less healthy lifestyle behaviors that become affordable during the acculturation process.